Increased levels of IL-10, IL-12, and IFN- in patients with visceral leishmaniasis - A. Khoshdel; A. Alborzi; M. Rosouli; E. Taheri; S. Kiany; M.H. Javadian (Brazilian Journal of Infectious Diseases)
Visceral leishmaniasis remains a serious public health problem in developing countries. Cytokines have a crucial role in the pathogenesis of this disease. We evaluated plasma levels of IL-10, IL-12 and IFN- in 32 patients with active visceral lieshmaniasis, in 29 siblings of the patients and in 23 normal individuals in an endemic area to look for correlations between the clinical outcome of infection and the plasma cytokine levels. An analysis was made with a skin test and a quantitative sandwich enzyme immunoassay. Data were analyzed with the Mann Whitney test and the Kruskal Wallis test. The cytokine levels were significantly higher in the patients than in the control groups. We concluded that normalization of the plasma level of IFN- can serve as a reliable parameter for considering the patient as cured.